Directional genomic hybridization (dGH™) identifies small inverted duplications in situ - Liehr, Thomas; Cross, Erin; Kankel, Stefanie (Frontiers in Genetics, 2025)
Although fluorescence in situ hybridization (FISH) is a standard approach for characterizing the chromosomal structure involving a region of interest, FISH targeting single chromatids is not routinely performed. However, this latter approach seems principally well-suited to distinguish small, tandem inverted duplications from direct duplications in clinical cases. A commercially available single-chromatid FISH approach, called “directional genomic hybridization” (dGH™), was applied in this study to nine cases of small supernumerary marker chromosomes (sSMCs) known to contain inverted duplications. Successful detection of small inverted duplications has been demonstrated for the first time in this study using a custom Kromatid dGH™ InSite Assay. In all five euchromatic sSMC cases, inversions were detected using the dGH single-chromatid molecular cytogenetic assay. Thus, the dGH method of FISH is a readily applicable, straightforward approach for identifying small inverted duplications that are undetectable by conventional (molecular) cytogenetic methods. This technique may be used to identify the presence of small inversions within regions presenting a copy number gain as detected by chromosome microarray. Distinguishing small inverted duplications from direct duplications may have an impact on topologically associating domains (TADs) and, thus, on clinical outcome.